Burdensharing and its discontents Understanding and optimizing allied contributions to the collective defense - Mallory, Charles King; Germanovich, Gene; Welburn, Jonathan William; Smith, Troy D. (RAND, 2024)
"New security challenges from Russia, China, North Korea, and Iran have reignited the perennial debate about whether U.S. allies in the North Atlantic Treaty Organization (NATO) and in Asia are contributing sufficiently to the collective defense of the post-World War II liberal international order. The debate, which had subsided after the Cold War ended, has once again become a high priority in the U.S. foreign policy agenda. However, the traditional standard for measuring allied contributions--military expenditures as a percentage of gross domestic product (GDP)--provides an incomplete analytic foundation for understanding burdensharing. At the request of the Office of the Secretary of Defense, RAND researchers reviewed the burdensharing debates and the associated literature and constructed a Burdensharing Index to aid in measurement and analysis. The index provides a more sophisticated picture of allied burdensharing than is possible when focusing solely on military spending as a percentage of GDP. The index also helps policymakers understand how they might incentivize additional allied commitments to generating the capabilities required for potential warfights, as identified in the 2018 National Defense Strategy (NDS). Although the U.S. share of the costs of collective defense in Europe and Asia is certainly disproportionate, the U.S. burden is not as lopsided as some have asserted. As estimated by the Burdensharing Index presented in this report, the United States bears slightly less than half (about 47 percent) of the total burden of providing the collective defense."
Keywords: NATO; Finanzierung; Mitgliedsstaaten; Militärpolitik; Verteilung; Militärausgaben; North Atlantic Treaty Organization / Armed Forces / Procurement; Military policy / International cooperation; Asia / Armed Forces / Procurement; United States / Armed Forces / Procurement; United States / Economic relations / 21st century; United States / Foreign relations / 21st century; United States / Military relations / 21st century; Global Security; International Economic Relations; Military Budgets and Defense Spending; North Atlantic Treaty Organization; HISTORY / Military / General; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Political Economy; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations); INTERNATIONAL RELATIONS; MILITARY BUDGETS